An Application of The PROMETHEE Method To Select The Best Response for Carbon Fibre Reinforced Plastic Drilling in Machining Operations - Oke, Sunday Ayoola; Odusoro, Salome Ifeoluwa (International Journal of Industrial Engineering and Engineering Management, 2021)
The manufacture of carbon fibre reinforced plastic (CFRP) composites from carbon fibres fused with epoxy matrix, deploying the hand layup method has raised considerable attention. Within this research domain, drilling with various tools such as coated and uncoated drills is of great significance. Unfortunately, the use of intuition and experience to select the best parameter in the drilling operation has been known to be less efficient, causing the inadequate distribution of drilling resources to actualize the effectiveness of drilling parameters. Energy wastages are also associated with the present practice of intuition in drilling process. In this study, a novel approach of PROMETHEE I and II are presented to avoid ineffectiveness in drilling resource distribution and select the best drilling operations parameters. The proposed method utilizes experimental data from the literature to verify the method's performance. This study helps in reducing waste due to the inadequate distribution of drilling operations sources. PROMETHEE analyses the drilling parameters of the CFRP composites using preference functions that map the differences among alternatives during machining judgments. Out of the six responses examined, the best response is exit delamination with a weight of 0.059, surface roughness with a weight of 0.031emerged as the second position, torque weighing 0.003 took the 3rd position while the last position is entry delamination, weighing -0.102.